USA-Croatian cooperation in education and training for public administration in Croatia - Thomas A. Cozzens; Helena Blažić; Marija Kaštelan-Mrak (Central European Public Administration Review)
For the past six years the Unger International Center for Local Government Leadership in the Maxine Goodman Levin College of Urban Affairs, Cleveland State University, Cleveland, Ohio USA, has been collaborating with the Faculty of Economics, University of Rijeka and USAID’s Local Government Reform Project to advance education and in-service training for local government officials in Croatia. This paper presents an in depth review and analysis of focusing on its successes and challenges and the application of lessons learned to the future of public administration education, training and professional development in Southeast Europe.